Trudności i wyzwania, z którymi zmierzyła się edukacja specjalna podczas pandemii - Czudek, Aleksandra; Głowacka, Kamila (Zeszyty Naukowe Pedagogiki Specjalnej, 2022)
The covid-19 pandemic has brought many changes in every sector of our life. Especially it concerned a special education and people with disabilities. Remote learning is responsible for many difficulties for disabled children, special educators and the functioning of special schools.